Therapeutic plasma exchange combined with immunomodulating agents in secondary progressive multiple sclerosis patients - Grapsa, E.; Triantafyllou, N.; Rombos, A.; Lagouranis, A.; Dimopoulos, M.-A. (Therapeutic Apheresis and Dialysis, 2008)
Multiple sclerosis (MS) is the most common cause of neurological disability. Therapeutic plasma exchange (TPE) has been used in the management of patients with MS with equivocal efficacy. With this work we would like to present our experience with 10 patients (seven male and three female, mean age 34 years [range 27-53 years]) with secondary progressive MS, who were treated with immunomodulating agents and who also underwent TPE. The patients' expanded disability status scale (EDSS) score of entry to the study varied from 5.0 to 6.5. One year before study entry all patients showed a marked deterioration (12 months before starting TPE they had been rated 4.5-5.5 on the EDSS). TPE was performed three times a week for two weeks and thereafter once a week, or once a month for the stable patients. The machine used was the Cobe Spectra and albumin 5% was the replacement fluid. Peripheral veins were used in nine patients and indwelling vascular access was required in one patient. Eighteen months later, patients stopped taking the immunomodulating agent therapy and continued only with TPE. No side-effects occurred during the TPE session. After 36 months of TPE therapy, five patients were stabilized in their disability, while two patients showed a minor progression of the disease (an additional 0.5 degree in disability as determined by the EDSS). No relapses occurred during TPE. Three patients stopped the therapy: one patient because of persistent nausea and two patients for reasons unrelated to TPE. Periodic TPE was associated with reduced accumulation of neurological deficits (as documented by EDSS) in patients with secondary progressive MS. © 2008 International Society for Apheresis.
Keywords: Autoimmune disorder; Disability; Immunomodulator; Multiple sclerosis; Plasmapheresis; Therapeutic plasma exchange